A break from traditional programs : ensuring the academic success of upper secondary immigrant students - Candace Alison Loque 1981- (2022)
The growing multicultural environment that schools at all school levels face needs teachers and educators who are willing and ready to change their teaching methods and are attentive to their students' needs. Even though the upper-secondary schools in Iceland are increasingly accommodating to immigrant students, recent data of student dropouts has demonstrated that professionals lack the knowledge and skills needed to successfully help this group of students move forward with their education. The purpose of this research is to understand how upper secondary school teachers work with students with diverse language backgrounds in order to construct a pedagogy that responds to immigrant students. The aim is to investigate how teachers employ the multicultural teaching approach with students with diverse language backgrounds. This is a qualitative study, and the data consists of 30 stories collected from upper secondary teachers, immigrants and upper secondary students using the story completion method. The stories were thematically analyzed. Findings reveal that anxiety, although for various reasons, was present in each group's combined stories. Teachers showed that they want nothing but the best for their students and are willing to find effective teaching methods. However, they felt that they lacked the skills to obtain this vision, as well as lacked support. Similarly, the immigrant group suggested that flexible and effective teaching methods are necessary for students to succeed academically. Acquisition of academic language skills was something that they agreed to be a crucial factor for progress. However, students' key results showed that they care more about their well-being than how they prepare themselves for academic success. Í því vaxandi fjölmenningarlega umhverfi sem skólar á öllum skólastigum standa frammi fyrir, þurfa kennarar að vera tilbúnir að breyta kennsluaðferðum sínum og hefðum til að bregðast við fjölbreyttum hópi nemenda. Jafnvel þó framhaldskólar á Íslandi séu í auknum mæli að reyna að ...